Inequality in Colonial India - Satish Saberwal (Contributions to Indian Sociology 1979; 13; 241, 1979)
It was a sense of puzzlement over contemporary India that led me initially into an Interest in inequality, but neither the many excellent analyses of the caste system nor the more recent statements on social stratification aided much in resolving this Puzzlement. Slowly I came to believe, first, that this inequality, if adequately Understood, would help establish sociological control over numerous other issues concerning the contemporary Indian social structure' and, second, that the roots of this inequality have to be located in the colonial experience. Here I work through the second proposition. Much of the treatment has to be excessively brief and tentative, but I hope to be able to make amends in the future.